(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In these working conditions, the education of the pedagogue is difficult for the "I" of teenagers to the problem of a psychological approach to the professional activity of correction is of particular importance due to its dedication. Within this problem problems of scientific theoretical approaches to the psychological analysis of professional activity is studied.